Maximal Oxygen uptake cannot be determined in the incremental phase of the lactate minimum test on a cycle ergometer - Miyagi, Willian Eiji [UNESP]; Malta, Elvis de Souza [UNESP]; Zagatto, Alessandro Moura [UNESP] (Journal Sports Science &medicine, 2015)
The aim of this study was to investigate the maximal oxygen uptake (VO2MAX) determined using the incremental phase of the lactate minimum test (LM) on a cycle ergometer. Fifteen trained men were submitted to a graded exercise test (GXT) to evaluate the VO2MAX and LM. The total durations of the GXT and LM were 11.2 +/- 1.8 minutes (CI95%: 10.2-12.3 minutes) and 25.3 +/- 3.2 minutes (CI95%: 23.5-27.0), respectively. For the variables measured at exhaustion in both the GXT and LM, the oxygen uptake (54.6 +/- 8.1 ml.kg(-1).min(-1) vs 50.0 +/- 7.7 ml.kg(-1).min(-1)), carbon dioxide production (66.1 +/- 7.5 ml.kg(-1).min(-1) vs 50.4 +/- 8.0 ml.kg(-1).min(-1)), ventilation (153.9 +/- 19.0 L.min(-1) vs 129.9 +/- 22.9 L.min(-1)), respiratory exchange ratio (1.22 +/- 0.10 vs1.01 +/- 0.05), maximal power output achieved (331.6 +/- 45.8 W vs 242.4 +/- 41.0 W), heart rate (183.1 +/- 6.9 bpm vs175.9 +/- 10.6 bpm) and lactate (10.5 +/- 2.3 mmol.L-1 vs 6.6 +/- 2.2 mmol.L-1) were statistically lower in the LM (p < 0.05). However, the values of rating of perceived exertion (17.6 +/- 2.5 for GXT and 17.2 +/- 2.3 for LM) did not differ (ES = 0.12 and CV = 7.8%). There was no good agreement between the values of the VO2MAX from the GXT and VO2PEAK from the LM, as evidenced in the Bland-Altman plot (4.7 ml.kg(-1).min(-1) and 0.34 L.min(-1) of mean differences, respectively), as well as the high values of the upper and lower limits of agreement. We conclude that the VO2PEAK values obtained in the incremental phase of the LM underestimate the VO2MAX.
Keywords: Maximal aerobic power; Aerobic capacity; Aerobic and anaerobic fitness